(untitled) (Research, Society and Development, 2022)
Aim: To compare the celerity of hospital access with percutaneous coronary intervention (PCI), use of primary PCI and 30-day mortality among patients with STEMI who initiated symptoms in the non-metropolitan region with those who started in the metropolitan region of the state of Aracaju. Method: A quantitative cohort study using data from the VICTIM registry from December 2014 to October 2017. A significance level of 5% was adopted (p<0,05). Findings: 878 patients participated in the study, of which 382 started the symptoms in the metropolitan region and 496 in the non-metropolitan region. The latter region traveled more distances (104 ± 58.4km vs. 16 ± 49.3km, p <0.001), passed more than 1 institution (96% vs. 73%, p <0.001), presented greater delay to the hospital (11h [7-26] vs. 7h [3-17], p <0.001) and therefore performed less primary PCI (45% vs. 59%, p <0.001). It was also observed that those from the non-metropolitan region had a higher chance of death at 30 days (OR 1.84, 95% CI, 1.12 to 3.04, p = 0.016). Conclusion: Disparities in access, use of primary PCI, and 30-day mortality rates observed among the groups analyzed. These findings may help to better delineate the logistics of access to reperfusion therapies in Sergipe.